2016
DOI: 10.1144/sp408.10
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic bioenergetics model-based approach to translating large river flow and temperature into fish population responses: the pallid sturgeon example

Abstract: In managing fish populations, especially at-risk species, realistic mathematical models are needed to help predict population response to potential management actions in the context of environmental conditions and changing climate while effectively incorporating the stochastic nature of real world conditions. We provide a key component of such a model for the endangered pallid sturgeon (Scaphirhynchus albus) in the form of an individual-based bioenergetics model influenced not only by temperature but also by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…This is supported by other modeling approaches in which a shift to higher quality prey fish by pallid sturgeon was necessary to attain growth rates observed in the field (Wildhaber et al. ). Moreover, fish prey comprises the majority of large (>50 cm) juvenile pallid sturgeon diets, indicating that young pallid sturgeon depend more on higher quality prey than shovelnose sturgeon (Gerrity et al.…”
Section: Discussionsupporting
confidence: 54%
“…This is supported by other modeling approaches in which a shift to higher quality prey fish by pallid sturgeon was necessary to attain growth rates observed in the field (Wildhaber et al. ). Moreover, fish prey comprises the majority of large (>50 cm) juvenile pallid sturgeon diets, indicating that young pallid sturgeon depend more on higher quality prey than shovelnose sturgeon (Gerrity et al.…”
Section: Discussionsupporting
confidence: 54%
“…Pallid sturgeon shift their diet from macroinvertebrates to fish between lengths of 500 and 700 mm, and are completely piscivorous by 700 mm (Gerrity et al., ; Grohs et al., ; Winders & Steffensen, ). Juvenile pallid sturgeon readily feed on diptera, ephemeroptera, decapoda, and trichoptera (Grohs et al., ; Winders & Steffensen, ), which have a mean caloric density of 3065.8 J/g compared to a caloric content of 4473.5 J/g (Wildhaber et al., ). To consume the caloric equivalent of a single, small‐bodied fish, a juvenile pallid sturgeon feeding on macroinvertebrates likely needs a longer forage period.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial focus of this study was the development of a stochastic bioenergetics model for fish growth. Specifically, to translate water velocity and temperature into fish growth, we implement a daily time step, individual-based, bioenergetics model for the endangered pallid sturgeon based on a basic pallid sturgeon bioenergetics model (Chipps et al 2008), combined with swimming energetics described for other sturgeon species (Geist et al 2005); a general description is given below (details of the model can be found in Wildhaber et al 2015). The parameters of the bioenergetics model were estimated through field study of pallid and other sturgeon species, extrapolated across different size classes or kept constant throughout the population (Tetzlaff et al 2011).…”
Section: River Flow and Temperature To A Bioenergetics Modelmentioning
confidence: 99%
“…Our bioenergetics model (as originally described by Kitchell et al 1977) (Wildhaber et al 2015) is fundamentally based on the following simple relationship that conserves energy input and output:…”
Section: Basic Bioenergetics Modelmentioning
confidence: 99%